Enhancing Electrochemical Performances of TiO2 Porous Microspheres through Hybridizing with FeTiO3 and Nanocarbon. (1st February 2016) - Guo, Shimei; Liu, Jiurong; Qiu, Song; Wang, Yiran; Yan, Xingru; Wu, Nannan; Wang, Shenyu; Guo, Zhanhu
Graphical abstract: Highlights: TiO2 /FeTiO3 @C hybrid porous microspheres have been synthesized. The as-prepared composites exhibit superior cycling and rate performances as LIBs anode material. The synergism among TiO2, FeTiO3 and carbon coating benefit the electrochemical performance. Abstract: The carbon-coated TiO2 (TiO2 @C) and FeTiO3 (TiO2 /FeTiO3 @C) hybrid porous microspheres with a specific surface area of 35.1 m 2 g −1 have been successfully synthesized by carbonizing the mixture of pyrrole with lab-made TiO2 /Fe2 O3 porous microspheres. The as-prepared TiO2 /FeTiO3 @C porous electrode material possessed a reversible capacity of 441.5 mAh g −1 after 300 cycles at a current density of 100 mA g −1 and a coulombic efficiency of 99%. Comparing with TiO2, TiO2 @C, and TiO2 /Fe2 O3 porous microspheres, the TiO2 /FeTiO3 @C porous composites exhibited superior cycling and rate performances, which are rooted in the synergistic effect that generated by little volume variation of TiO2 matrix, high capacity of FeTiO3 and good electrical conductivity of carbon coating (with a thickness of 2–5 nm deposited on the surface and inner wall of pores) during the charge/discharge processes.